1970
DOI: 10.1002/app.1970.070140812
|View full text |Cite
|
Sign up to set email alerts
|

Studies on tack of pressure–sensitive adhesive tapes

Abstract: SynopsisI t has been found that tack values of pressure-sensitive adhesives are dependent on the surface energies for adherends. The parabolic curves with maxima are obtained from the plots of tack values versus crit,ical surface tensions for the substrates. The maximum occurs a t the region where the two surface tensions are almost similar. On the other hand, tack is measured as a dynamic value indicated as the force necessary to deform the adhesive mass. To explain why the tack values is controlled by the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…The distribution cp( z ) is then given by With this distribution, the total area of contact and the total load are given by A,,, = naR ( 8 ) P,,, = nEa3/'R'/'. (9) From these two expressions, one can easily obtain the relationship between load and area: which gives the well-known Greenwood result that the area of contact and the applied pressure are proportional to each other. 13 The important result that should be emphasized in our context is that for a given surface, A is inversely proportional to the elastic modulus E and proportional to the applied pressure.…”
Section: Large Pressuresmentioning
confidence: 99%
“…The distribution cp( z ) is then given by With this distribution, the total area of contact and the total load are given by A,,, = naR ( 8 ) P,,, = nEa3/'R'/'. (9) From these two expressions, one can easily obtain the relationship between load and area: which gives the well-known Greenwood result that the area of contact and the applied pressure are proportional to each other. 13 The important result that should be emphasized in our context is that for a given surface, A is inversely proportional to the elastic modulus E and proportional to the applied pressure.…”
Section: Large Pressuresmentioning
confidence: 99%
“…However, the correlation was less well established for PSAs. Toyama and co-workers studied the probe tack and peel strength of a poly(?z-butyl acrylate) on a variety of substrates and analyzed the dependence of their data on the surface energy of the adherends (Toyama et al, 1970). They found a maximum in the peel strength when the surface tensions of the adhesive, y a , and of the adherend, y s , were closely matched and argued that in this situation the interfacial energy is minimum.…”
Section: Surface Properties Of the Substratementioning
confidence: 99%
“…For example, Toyama et d Z 8 found that tack and peel adhesion were influenced by the difference between the surface tensions of the adhesive polymer and adherend. The pattern of peel morphology may, therefore, also be related to the difference between the surface tensions of the acrylate polymers.…”
Section: Surface Tensionmentioning
confidence: 99%